HUBUNGAN ANTARA PARITAS DAN UMUR IBU DENGAN PEMBERIAN MP-ASI DINI PADA BAYI UMUR < 6 BULAN - Rosi Kurnia Sugiharti (Viva Medika, 2017)
Abstract WHO recommendations on exclusive breastfeeding until the age of 6 months seem to be still difficult to implement. Based on reports of exclusive breastfeeding in Banyumas District in 2014 was 20.90%. Based on Banyumas District report 2014, the region with the lowest exclusive ASI coverage is Purbadana Village, which is 5%. Some of the factors behind the introduction of early breastfeeding include knowledge, education, parity, occupation, socio-economic, and age. The purpose of this study is to determine the factors behind the mother to give early breastfeeding in infants under 6 months in the Village Purbadana Kembaran District Banyumas District in 2017. The method in this research is corelational analytics with case control approach. A sample of 60 respondents was taken using total sampling. Data were collected using questionnaire, then analyzed using frequency distribution and Chi Square and Kolmogorov Sminorv. The results showed that there was a relationship between the parity of mothers with a significance value of 0.020. Maternal factors that are not associated with early breastfeeding are age with p value 0,459. The resulting output is a scientific publication in the Journal of Viva Medika Keywords: Relationship, Age, Parity, Early MP-ASI